Features of forming of political competence of future officers are in Ukraine - Kuruch, A (Problems of Engineer-Pedagogical Education, 2019)
The article considers the peculiarities of forming the political competence of the Ukrainian population, in particular future officers. A comparative analysis with the leading countries of the world is made. The current geopolitical situation in Ukraine is analyzed, the conclusion is made about the inadequacy of the formation of political culture among the population of the country. The role of political culture in forming the political competence of the Ukrainian population is analyzed. The necessity of forming political competence among the Ukrainian population, in particular among the students of higher military educational institutions, is analyzed. The historical features of the formation of the political culture of the population of Ukraine are analyzed. The necessity of further introduction of cadets' political competence in teaching is emphasized. The necessity of reforming the system of higher military education is emphasized. Conclusions regarding the further introduction of the competency model into training are made. The necessity of further scientific and theoretical substantiation of the development of the problem of political competence of cadets of higher military educational institutions is emphasized. The issue of hybrid war on the territory of Ukraine, and the need for the introduction of political training to protect the national identity of the country are revealed.